IMPLEMENTASI IMT-GT VISION 2036 DALAM MENINGKATKAN PARIWISATA MARITIM DI KEPULAUAN RIAU - Ramadhan, M. Gillang; Fuadi, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
This study analyzes the implementation of the Indonesia–Malaysia– Thailand Growth Triangle (IMT-GT) Vision 2036 in efforts to enhance maritime tourism in the Riau Islands Province. IMT-GT Vision 2036 serves as a long-term strategic framework that emphasizes the strengthening of connectivity, sustainable economic growth, and regional competitiveness through the development of priority sectors, including tourism. As one of the strategic regions within the IMT- GT framework, the Riau Islands Province possesses significant maritime potential, characterized by its location along international shipping routes and the presence of diverse marine tourism destinations. This study employs a descriptive method using a qualitative research approach, with data collection techniques carried out through a literature review sourced from books, journals, articles, and websites. The research applies the theory of International Cooperation and the concept of regional cooperation. The findings of this study indicate that during the pre-intervention stage, the maritime tourism potential of the Riau Islands was not supported by optimal destination management and connectivity. In the development stage, the Working Group on Tourism (WGT) promoted the implementation of tourism strategies through the integration of the blue economy concept, the strengthening of connectivity, and sub-regional promotion in line with the direction of IMT-GT Vision 2036. In the outcome stage, these initiatives resulted in improvements in destination quality, tourism accessibility, and the competitiveness of maritime tourism in the Riau Islands, while simultaneously reinforcing its position as Indonesia’s maritime gateway. This study concludes that the Riau Islands Province serves as a concrete example of the successful implementation of cross-border cooperation that generates mutual benefits, including an increase in tourist arrivals, growth in tourism sector investment, and the strengthening of economic capacity among coastal communities. Keywords: Maritime tourism, IMT-GT, Working Group Tourism, Implementation.